PENERAPAN E-LEARNING SOCRATIVE DALAM PEMBELAJARAN BAHASA - Alfa Mitri Suhara; Dida Firmansyah; Indra Permana (Jurnal Semantik, 2019)
The world of education in the era of the industrial revolution 4.0 is developing dynamically. This is a challenge for the education sector to produce critical, creative, innovative, communicative human resources who can collaborate, collaborate, and be confident. Therefore, education must be able to answer these challenges. ICT-based learning (Information Communication Technology) is a medium or learning aid that can be used in the era of the industrial revolution 4.0. One of ICT-based learning through e-learning scorative, namely active learning media that involves students directly through applications by utilizing the ADDIE system. E-learning socrative that can be used in practical learning. In this study specifically used in language learning. The purpose of this study is to determine the differences before and after the application of e-learning socialization in language learning and the learning process. The study was conducted at IKIP Siliwangi with a sample of 25 students of the Indonesian language study program. The research method uses a quasi-experimental type one group pretest-posttest design with data collection techniques through tests and observations. The results showed that the language learning process was effective and enthusiastic. The results of the average test stated there were differences before and after the application of e-learning system in language learning with an average initial test score of 55.04 and final test 62.48.